A Note on the Names for Winter Storms. (December 2015) - Nuessel, Frank
Abstract : This note reviews briefly the history of naming tropical storms. It then discusses the very recent and sometimes controversial phenomenon of naming winter storms. Finally, a list of the most recent designations for winter storms is provided.